Data Science Approach for Social Media Analytics - Kavya.V, N. Harini (International Journal of Advanced Science and Technology, 2020)
Today there is an exponential growth and widespread dependence of users on digital social media.Deep learning has gained increased attention because of its huge processing power and data analyticscapability. Many works in the literature has focused on risks associated with sharing sensitive datausing Machine learning models to understand human behavior. An attempt has been made in this workto evaluate the performance of Deep learning model to understand human behavior. Theexperimentation results clearly reveal that Deep learning models provide a better prediction forcontrolling the dynamics of information spread among peers